2022
DOI: 10.1371/journal.pone.0272732
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of psychological interventions for reducing PTSD and psychological distress in first responders: A systematic review and meta-analysis

Abstract: Background First responders are faced with stressful and traumatic events in their work that may affect their psychological health. The current review examined the effectiveness of psychological interventions to treat posttraumatic stress disorder (PTSD), anxiety, depression, stress and burnout in first responders. Methods Four databases were searched to identify controlled studies that examined the efficacy of psychological interventions to reduce PTSD symptoms (primary outcome) in first responders (includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Recent literature has studied public safety personnel, especially emergency health workers, military personnel, firefighters, and law enforcement. Published literature has recorded a prevalence of any mental health condition from 6.4% to 57% for firefighters [9,10], 3.72% to 37.8% for military personnel [10][11][12], and 5.8% to 19.6% for police officers [9,13,14]. Prevalence is dynamic and these range of prevalence could be attributed to sample size, population, methodology, or time [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has studied public safety personnel, especially emergency health workers, military personnel, firefighters, and law enforcement. Published literature has recorded a prevalence of any mental health condition from 6.4% to 57% for firefighters [9,10], 3.72% to 37.8% for military personnel [10][11][12], and 5.8% to 19.6% for police officers [9,13,14]. Prevalence is dynamic and these range of prevalence could be attributed to sample size, population, methodology, or time [10].…”
Section: Introductionmentioning
confidence: 99%
“…Authors of a meta-analysis [ 33 ] of police stress reduction programs concluded that, “insufficient evidence exists to demonstrate the effectiveness of stress management interventions for reducing negative physiological, psychological or behavioral outcomes among police officers.” (p. 508). More recently, in a 2022 meta-analysis of behavioral health interventions [ 34 ], authors found collectively these interventions did not reduce stress across LEOs, firefighters, paramedics, and EMTs. Relatedly, LEOs face a number of barriers to seeking mental health services, including stigma and concerns regarding confidentiality, resulting in low use of these services [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The re ghting community-including re ghters, paramedics, EMTs, and dispatch-have increased risk for traumatic exposure, but re service members are underrepresented in the traumatic stress literature [4,5,6,7,8,9]. In addition to high rates of PTSD, many may suffer from symptoms associated with PTSD without meeting full criteria for PTSD (i.e., partial or sub-threshold PTSD), highlighting the need to capture posttraumatic symptomatology in this population [10,11].…”
Section: Introductionmentioning
confidence: 99%